Similar Evolutionary Trajectories for Retrotransposon Accumulation in Mammals. (4th September 2017) - Buckley, Reuben M.; Kortschak, R. Daniel; Raison, Joy M.; Adelson, David L.
Abstract: The factors guiding retrotransposon insertion site preference are not well understood. Different types of retrotransposons share common replication machinery and yet occupy distinct genomic domains. Autonomous long interspersed elements accumulate in gene-poor domains and their nonautonomous short interspersed elements accumulate in gene-rich domains. To determine genomic factors that contribute to this discrepancy we analyzed the distribution of retrotransposons within the framework of chromosomal domains and regulatory elements. Using comparative genomics, we identified large-scale conserved patterns of retrotransposon accumulation across several mammalian genomes. Importantly, retrotransposons that were active after our sample-species diverged accumulated in orthologous regions. This suggested a similar evolutionary interaction between retrotransposon activity and conserved genome architecture across our species. In addition, we found that retrotransposons accumulated at regulatory element boundaries in open chromatin, where accumulation of particular retrotransposon types depended on insertion size and local regulatory element density. From our results, we propose a model where density and distribution of genes and regulatory elements canalize retrotransposon accumulation. Through conservation of synteny, gene regulation and nuclear organization, mammalian genomes with dissimilar retrotransposons follow similar evolutionary trajectories.